2014
DOI: 10.4103/1947-2714.128476
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between type 2 diabetic retinopathy and periodontal disease in Iranian Adults

Abstract: Background:Periodontal disease in diabetic patients can compromise a patient's ability to maintain a proper metabolic control and may be associated with diabetic complication.Aims:This study was designed to evaluate the frequency of periodontal disease in patients with type 2 diabetes mellitus (DM) and how this was related with the presence of diabetic retinopathy (DR).Materials and Methods:A comparison was made of periodontal parameters (plaque index (PI), community periodontal index of treatment needs (CPITN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
(32 reference statements)
2
24
0
Order By: Relevance
“…The present prospective cross-sectional study involved 200 adult diabetic patients (144 males and 56 females), of whom 151 presented with DR of varying severity. In our study, the mean duration of type II DM was directly correlated with the severity of DR. A similar association was found in a study by Amiri et al, who reported a mean duration of DM of 10.5 years [6]. A similar correlation was also found in another study by Noma et al, in which the mean duration of DM reported was 14.3 years [20].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present prospective cross-sectional study involved 200 adult diabetic patients (144 males and 56 females), of whom 151 presented with DR of varying severity. In our study, the mean duration of type II DM was directly correlated with the severity of DR. A similar association was found in a study by Amiri et al, who reported a mean duration of DM of 10.5 years [6]. A similar correlation was also found in another study by Noma et al, in which the mean duration of DM reported was 14.3 years [20].…”
Section: Discussionsupporting
confidence: 86%
“…It is estimated that almost half of the world’s population of diabetics will develop a degree of DR at some point in their lifetime. The incidence and risk of progression of DR have declined during the past 30 years, from 90% to less than 50%, due to improvements in medical care [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of our analysis agree with that of the studies done by Collin's et al . [ 13 ] and Avideh Maboudi[ 16 ] (2014), but they disagree with the results found in the studies conducted by Aydin et al . [ 17 ]…”
Section: Discussionmentioning
confidence: 75%
“…Most of these studies included small numbers of subjects and did not consider possible confounders. [ 8 , 9 ] One study performed among 100 patients with type 2 diabetes found that the oral hygiene score, probing pocket depth, and clinical attachment loss were significantly different between patients with and without diabetic retinopathy; however, after adjusting for confounders, these results failed to show significant effects. [ 6 ] As diabetic retinopathy is the most common cause of blindness among the working population worldwide, evaluating the relationship between diabetic retinopathy and periodontal disease will provide important clinical information for persons with diabetes, [ 10 12 ] and this information may help improve the socioeconomic burden caused by diabetes-related complications in the future.…”
Section: Introductionmentioning
confidence: 99%